(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
The article analyzes the dynamics of orthographic norms in contemporary Russian and identifies key trends in their development. It examines linguistic and extralinguistic factors that contribute to spelling instability, as well as challenges in implementing the norm in writing practice. Particular attention is paid to the orthography of loanwords as one of the most variable areas of modern written usage.